Application of Certified Superior Rice Seed Technology to Increase Organic Rice Production Farmer group in Cipatujah sub-district - Permana, Indra; Suryaman, Maman; Amilin, Amir; Zumani, Darul; Mustofa, Romy Faisal (Jurnal Biologi Tropis, 2024)
Improving the production of organic rice can be achieved by using certified superior seed varieties. The research aimed to test the adaptability of several superior rice varieties in organic farming systems to obtain varieties suitable for rice growth and yield in the Cipatujah District of Tasikmalaya Regency. A single-factor randomized complete block design was used in this study to test 3 superior varieties, namely Ciherang, Inpari 32, and Mekongga varieties. Each treatment was replicated 20 plots, resulting in a total of 60 experimental plots. The analysis results indicated that the soil at the demonstration plot location met land suitability and rice plant growth requirements with S1 (very suitable) criteria based on parameters such as pH, organic carbon content (C-organic), nutrient content of Nitrogen, Phosphor, and Potassium, bulk density, particle density, porosity, and soil texture. The superior variety treatments had a significant impact on plant height growth, although there were no significant differences observed in terms of tiller number, productive tiller number, grain yield per hill, filled grain per hill, grain weight per hill, and 1000-grain weight. The Ciherang variety showed the highest plant growth response and larger yield components compared to Mekongga and Inpari 32. The use of certified seeds in organic rice cultivation practices was proven to yield higher results compared to seeds from previous cultivation practices.